Self‐Powered UV Photodetectors With Ultrahigh Performance Enabled by Graphene Oxide‐Modulated CuI Hole Transport Layer - Baofen Cen; Yabing Wang; Hongrong Zhang; Mingfen Mao; Tengfei Wang; Kaixiang Liu; Qinghong Li; Jing Zhang; Shengyun Luo; Guangcan Luo (Advanced Electronic Materials)
Abstract The hole transport layer (HTL) with a function of charge extraction and transport plays a pivotal role in enhancing the performance of ultraviolet photodetectors (UV PDs). Herein, a CuI p‐type layer modified with graphene oxide (GO) is efficiently employed as the hole extractor for UV PDs based on ZnO nanorod arrays (NRs). The UV PD fabricated on FTO/ZnO NRs/CuI@GO/Au architecture exhibits exceptional performance characteristics including remarkably high responsivity (up to 387 mA W−1), significant specific detectivity (1.7 × 1013 cm Hz1/2 W−1), and rapid rise/decay time (23/16 ns) under self‐powered mode. The presence of GO effectively adsorbs and aggregates CuI nanoparticles, resulting in the formation of compact films and reduction in surface trap defects. Furthermore, owing to the strong electronegativity of GO terminated oxygen‐containing groups, the work function and band structure of CuI are further optimized, which strengthens the built‐in electric field of the ZnO/CuI heterojunction. Meanwhile, the pyroelectric effect of CuI that obstructs the hole transport is suppressed with the addition of GO. These improvements not only improve charge separation and hole extraction efficiencies but also significantly mitigate surface nonradiative charge recombination. This approach provides a novel strategy for optimizing CuI as an immense potential HTL with GO modulation.